Efficient Synthesis of the Key Intermediate of Scopolamine by [4+3] Cycloaddition Reaction - Duan, Xiuyuan; Wang, Qian; Shahab, Muhammad; Liang, Chaoqun; Li, Gudong; Zheng, Guojun (Letters in Organic Chemistry, 2023)
Scopolamine, as an anticholinergic agent, plays a regulatory role in the peripheral nervous system. In this paper, 6,7-dehydrotropinone, which is the key intermediate of scopolamine, is synthesized in moderate yield through [4+3] cyclization reaction and Barton deoxygenation reaction. This route has good application prospects with mild reaction conditions, moderate yield, and simple operating procedures.
Keywords: better application perspective